Integrating HPV vaccination programs with enhanced cervical cancer screening and treatment, a systematic review. (31st March 2022) - Wirtz, Charlotte; Mohamed, Yasmin; Engel, Danielle; Sidibe, Anissa; Holloway, Megan; Bloem, Paul; Kumar, Somesh; Brotherton, Julia; Reis, Veronica; Morgan, Christopher
Abstract: A WHO global strategy launched in November 2020 sets out an ambitious pathway towards the worldwide elimination of cervical cancer as a public health problem within the next 100 years. Achieving this goal will require investment in innovative approaches. This review aims to describe integrated approaches that combine human papillomavirus (HPV) vaccination and cervical cancer screening in low- and middle-income countries (LMIC), and their efficacy in increasing uptake of services. A systematic review was conducted analyzing relevant papers from Embase, Medline, CINAHL and CAB Global Health databases, as well as grey literature. Narrative synthesis was performed on the included studies. Meta-analysis was not appropriate due to the heterogeneity and nature of included studies. From 5, 278 titles screened, 11 uncontrolled intervention studies from four countries (from Africa and east Asia) were included, all from the past 12 years. Four distinct typologies of integration emerged that either increased awareness of HPV and/or cervical cancer screening, and/or coupled the delivery of HPV vaccination and cervical cancer screening programs. The synthesis of findings suggests that existing HPV vaccination programs can be a useful pathway for educating mothers and other female caregivers about cervical cancer screening; through in person conversations with care providers (preferred) or take-home communications products. Integrated service delivery through outreach and mobile clinics may overcome geographic and economic barriers to access for both HPV vaccination and cervical cancer screening, however these require significant program and system resources. One study promoted HPV vaccination as part of integrated service delivery, but there were no other examples found that examined use of cervical cancer screening platforms to promote or educate on HPV vaccination. This review has demonstrated gaps in published literature on attempts to integrate HPV vaccination and cervical cancer screening. The most promising practices to date seem to relate to integrated health communications for cervical cancer prevention. Future research should further explore the opportunities for integrated health communications to support the efforts towards the new global cervical cancer elimination agenda, and costs and feasibility of integrated service delivery for underserved populations.